A intervenção estatal na economia através de sociedades de propósito específico e seus mecanismos de controle - Fontoura, Pedro Burdman da (2020)
This dissertation analyzes two distinct moments of state intervention in the economy: the creation of special purpose entities and, after their establishment, the control exercised over them. More specifically, the control instruments applied for the creation, operation and extinction of these companies are evaluated. For this, it is analyzed, from the dogmatic point of view, if the creation or extinction of the special purpose entities can be carried out by unilateral act of the Executive Branch, or if, on the contrary, they are complex acts, dependent on previous legislative authorization. Overcoming this analysis, is addressed the research problem of this dissertation: which are the implications of greater state intervention in the economy through special purpose entities, in terms of control over the creation, functioning and extinction of these entities? The possible increase of state participation in the economy is gauged by the increase in the number of special purpose entities within the state-owned companies and the increase in the amounts managed by these entities. Control mechanisms are analyzed for their compulsory existence and effective implementation, as well as for their specific ability to prevent infringements of various kinds. It is hypothesized that state intervention in the economy through special purpose entities, as currently practiced, has made it difficult for the competent bodies to control and supervise the use of public resources. The first justification of this dissertation is related to the possible need of prior and specific authorization of the Legislative Branch for the increase of the state participation in the economy through special purpose entities. In this case, the concern is with respect for the principle of separation of powers and the checks and balances mechanisms provided for in the Federal Constitution. The second justification concerns the control mechanisms currently applied for the creation, operation and extinction of special purpose entities. At this point, recent cases of infringements of various kinds, especially criminal and environmental, have drawn attention to the existence of possible failures in the control of these entities. The subject will be approached through doctrinal, jurisprudential and empirical analysis, the latter through case studies. In addition, proposals will be presented for better control of the special purpose entities.